Dietary beta‐carotene and lutein metabolism is modulated by the APOE genotype. (4th April 2016) - Huebbe, Patricia; Lange, Jennifer; Lietz, Georg; Rimbach, Gerald
Abstract: The human apolipoprotein E ( APOE ) genotype has been suggested to interact with nutrient metabolism particularly with lipid soluble vitamins. Plasma carotenoid levels are determined by numerous dietary and genetic factors with high inter‐individual variation; however, the APOE genotype has not been systematically examined so far. Our aim was to investigate the effect of the APOE genotype on dietary carotenoid metabolism with special regard to transcriptional regulation of carotenoid absorption, cleavage and adipocyte fat storage. We supplemented targeted replacement mice expressing human APOE3 and APOE4 isoforms with dietary beta‐carotene (BC) and lutein (LUT) for 8 weeks. Plasma BC and adipose tissue BC and LUT levels were in trend lower in APOE4 than APOE3 mice, while hepatic expression of the beta‐carotene oxygenases BCO1 and BCO2 was significantly higher. In contrast to the liver, mRNA levels of proteins involved in carotenoid absorption and cleavage in the small intestinal mucosa as well as of adipogenic markers in the adipose tissue were not different between APOE3 and APOE4 mice. Our data suggest that the hepatic carotenoid cleavage activity is higher in APOE4 mice partially reducing the circulation and extra‐hepatic accumulation of intact carotenoids as compared to APOE3. Therefore we suggest considering the APOE genotype as modulator of carotenoid status in the future. © 2016 BioFactors, 42(4):388–396, 2016